The Human Right to Housing in the Face of Land Policy and Social Citizenship : A Global Discourse Analysis - Kolocek, Michael (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores the human right to housing, presenting the findings of a global discourse analysis to analyse the right to housing from the perspective of theories on land policy and social citizenship. The book concludes that planners and policy makers will not be able to completely fulfil the human right to housing. For that reason, the book presents a theory of de-commodification of land use that highlights the meaning of land use rights for people affected by inadequate housing. Students and scholars across a range of disciplines, including social policy, global social policy, human rights law, discourse theory, and sociology will find this study of interest.